Deteksi Dini Kanker Payudara dengan Pemeriksaan Payudara Klinis (SADANIS) - Gusriani Gusriani; Nurrahmi Umami; Rusniati Rusmiati; Gusni Fitri (Universitas Borneo Tarakan, 2023)
Breast cancer is cancer that forms in breast tissue. One of the many cancers that cause death throughout the world. Delay in early detection is one of the causes of late treatment in patients with breast cancer. So far, breast self-examination or (BSE) is a fairly effective way of early detection of breast cancer. BSE is easy to do and can be applied to all ages, both teenagers and adult women. The aim is to do community service as a first step in preventing breast cancer by increasing the knowledge of women of childbearing age (WUS) about BSE. The community service was carried out with a total of 15 WUS participants with 2 stages, namely counseling about the importance of BSE as an initial stage and the next stage clinical breast examination as a first step in the early detection of breast cancer. The result of this service is the increasing knowledge of WUS regarding efforts to prevent breast cancer with early detection that is easy to implement and do yourself with BSE. Furthermore, no signs of breast cancer were found in the participants who underwent clinical examination (SADANIS). This community service activity is useful as an effort to prevent an increase in the rate of breast cancer patients by detecting it as early as possible.